PENGETAHUAN DASAR DESAIN TIGA DIMENSI SEBAGAI CARA MAHASISWA DESAIN UNTUK BERPIKIR BENTUK RUANG DAN VOLUME - R. Tosan Tri Putro (ATRIUM: Jurnal Arsitektur, 2017)
Title: Three Dimensional Basic Design Knowledge as Thinking Tools for Understanding the Shape, Space and Volume The consciousness of observing the shape and space of an object, whether large or small, is the sensitivity that becomes a designer of three-dimensional objects. A product form is created with full awareness by the designer, not by itself appearing. In addition to the function of the design object, in a design process there is a styling stage, aesthetic value visually, a form that follows the function or shape that follows the material. Aesthetic value in a design product that can not be separated from the ability of the designer with visual experience. The ability and sensitivity to observe and create an aesthetic visual form should be instilled since someone declares himself to be a designer or planner. Design areas such as architecture, interior, urban design, area and also design product are demanded for their ability to sensitize observing and design a space, volume and shape. This study is based on observations on a group of design students and literature studies. Based on observations over time, the spatial thinking capacity of each person is different, as is the ability to create an aesthetic value in a design. Everyone has different absorbtive power and creativity.